"Like I'm flying": Capoeira dance experiences of youth with visual impairments. (May 2023) - Esatbeyoglu, Ferhat; Kirk, TN; Haegele, Justin A
Participation in dance programs is associated with physical and psychosocial health among individuals with and without disabilities. However, literature centered on the dance participation experiences of youth with visual impairment remains scarce. Therefore, the purpose of this study was to explore the experiences of youth with visual impairments in a 3-week capoeira dance program. Fourteen adolescents with visual impairments (eight boys, six girls, aged 13–18 years old) were selected for participation in this qualitative inquiry. Participants engaged in a specially designed capoeira dance program led by trained instructors and volunteers in a metropolitan area in Turkey. The primary sources of data were semi-structured participant interviews completed after the conclusion of the program. Data were analyzed using a six-step thematic approach and recurrent themes were presented as findings. The authors constructed three themes in the data: (a) "capoeira makes me feel like I'm flying": fun and freedom learning capoeira; (b) "I've never had this kind of close relationship with somebody": relationships in capoeira training; and (c) "I'm a blind dancer. I did it, right?": learning capoeira through sound and touch. Together, these findings indicate that dance programs such as capoeira can provide an opportunity for social connection, enjoyment, and physical activity for youth with visual impairments.